Knowledge, Attitude, and Practice Regarding High Salt Intake and Association With Hypertension Among Rural Women in Chandpur District of Bangladesh - Pradip Chandra; Aminul Islam; Shahara Robertson; Abu‐Al‐Rafe; Md. Abu Sayed; Afra Anjum Ahona; Mst. Nadira Parvin; Pradip Sen Gupta (Health Science Reports)
ABSTRACT Background and Aims The human body requires a relatively little quantity of sodium to transmit nerve impulses, contract and relax muscles, and maintain appropriate water and mineral balance and which is typically added from diets. The study aimed to assess the level of knowledge, attitude, and practice regarding high salt intake and their association with hypertension among rural women of a selected community in Chandpur. Methods A cross‐sectional study was adopted to collect data from 250 households of Chandpur district. The study was conducted during May 2022 to July 2022. The semi‐structured pretested WHO‐modified step‐wise approach to the non‐communicable disease risk factor surveillance (STEPS). Instrument version 3.1 module was used to administer the knowledge, attitude and practice questionnaire to assess the knowledge, attitude and practice of the participants. Binary logistic regression was performed to examine the factor related with knowledge, attitude, and practices. Results The result gives evidence that participant who added always salt to their meals were three times more likely to be hypotensive (AOR: 2.99; CI: 1.40, 6.42). Besides, participants who avoid eating outside are significantly less likely (AOR: 0.19; C.I: 0.05 to 0.70) to be hypertensive. Conclusion Findings showed that daily salt consumption and “avoid eating out” were significantly associated with hypertension status. These findings imply that further educational intervention is needed to increase understanding of healthy dietary salt intake among rural women.